ОПАНАС СЛАСТЬОН ЯК ДОСЛІДНИК ОБРАЗОТВОРЧОЇ СПАДЩИНИ КОБЗАРЯ (Педагогіка вищої та середньої школи, 2007)
The article gives a broad outline of Slastion's publications investigating Shevchenko’s painting and graphic works. Shevchenko’s paintings are considered to be an indispensable constituent of the process coming into being and developing the art science that deals with particular historic period.